HUMAN TRAFFICKING IN THE FRAMEWORK OF THE INTERNATIONAL ADOPTION SYSTEM – AN (UN)SOLVABLE PROBLEM - Radišić, Milica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The article examines the relationship between human trafficking and intercountry adoptions from the point of perspective of international (criminal) law. The main objective of the article is to indicate the specific position of intercountry adoptions in the context of human trafficking, on the one hand, as well as the complexity of their relationship and the need for regulation, on the other hand. For this purpose, the article presents the ideas and arguments of the authors who examined the aforesaid relationship, concerning present (international) documents in the field of human trafficking and intercountry adoptions. However, although the aim of the article is not to answer the question of whether intercountry adoption is, per se, a form of human trafficking, in the end, as a significant obstacle to the study of intercountry adoptions, and their relationship with human trafficking, the lack of agreement among the authors themselves is identified, specifically to the question of the definition of key terms. Rexamination and reform of international law in the area of human trafficking and intercountry adoptions, with the prior introduction of new terms and their definition, is recognized as an adequate solution. Key words: human trafficking, international adoptions, children, disagreement, reform